The Modelling Studies of Ecological Corridor Management of The Gunung Halimun Salak National Park, West Java, Indonesia - Istiadi, Yossa; Retnowati, Rita; Pranowo, Agus Setya; Situmorang, Marningot Tua Natalis; Junanto, Try (UIN Fatmawati Sukarno Bengkulu, 2024)
This research aims to study the design of the ecological corridor management pattern of Gunung Halimun Salak National Park (TNGHS) through the identification of population and distribution of conservation species, edge effect of road access within the corridor, preservation mitigation, status of non-conservation species, and assessment of land-use-based ecotourism. The methods used include Belt transect, hypothetical transect, Intensive Point Account (IPA), and descriptive survey techniques. The research was conducted from September to December 2023. The results showed that the population density of Javan Gibbon was 0.114 indv/ha, Surili was 0.024 indv/ha, which is very low compared to the population density of TNGHS, 26 non-conservation bird species, and 1 endemic species, the Javan Gibbon. The edge effect is caused by the frequency of vehicles passing through the corridor. The hypothetical transect shows that the land use allocation for tea plantations is the target of ecotourism, and agricultural land use supports the product. The model design emphasizes the creation of protection zones for primates and Javan Eagles in terms of mobilization and migration, mitigation of vehicle crossings during the day, as well as the initiation of ecotourism based on non-conservation species and landscape characteristics. In conclusion, the ecological corridor management modeling includes accommodating the protection of endemic and rare animals, monitoring non-conservation bird species, conservation mitigation through vehicle frequency control, limited ecotourism development with a natural orientation, and agricultural products. Scientifically the contribution of this research is to explain the implications of island geography theory in the sustainability of endemic species in metapopulations to avoid genetic flow deviations.